STRUKTUR BIAYA DAN SKALA USAHA EKONOMIS PENGGILINGAN KOPI BUBUK DI KOTA BENGKULU - Romdhon, M. Mustopa (Jurnal AGRISEP, 2009)
The coffee has an economic prospective for Bengkulu PDRB since it is regional key commodity. But limitation of capital, production technology, and market information have made this business on stagnation condition. The research is aimed to elaborate the economic scale of coffee processing at Bengkulu Municipal. Processing coffee industries at Bengkulu city face with finacial, production technology and market information burdens,generally. Its later affect to the industrys’ economic scale Commonly, the processoris stil in decreasing return to scale,where the optimalitation on production factors usage could lead the processor to optimal capacity of production.